2014
DOI: 10.1186/1756-0500-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Arresting rampant dental caries with silver diamine fluoride in a young teenager suffering from chronic oral graft versus host disease post-bone marrow transplantation: a case report

Abstract: BackgroundRampant caries is an advanced and severe dental disease that affects multiple teeth. This case describes the management of rampant caries in a young teenager suffering from chronic oral graft versus host disease after allogeneic bone marrow transplantation.Case presentationA 14-year-old Chinese boy suffering from β–thalassemia major was referred to the dental clinic for the management of rampant dental caries. An oral examination revealed pale conjunctiva, bruising of lips, and depapillation of tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…The more often a child felt pain in his/her teeth, the lower the percentage of arrested caries found on the child. This research is consistent with a previous study that showed that SDF application was effective in overcoming toothaches caused by dentin hypersensitivity due to caries [8]. Caries are closely related to a child's ability to speak, mastication, social development, and quality of life [9].…”
Section: Discussionsupporting
confidence: 81%
“…The more often a child felt pain in his/her teeth, the lower the percentage of arrested caries found on the child. This research is consistent with a previous study that showed that SDF application was effective in overcoming toothaches caused by dentin hypersensitivity due to caries [8]. Caries are closely related to a child's ability to speak, mastication, social development, and quality of life [9].…”
Section: Discussionsupporting
confidence: 81%
“…From the 11 eligible papers, 5 were at low risk of bias [Yee et al, 2009b;Liu et al, 2012;Zhi et al, 2012;dos Santos et al, 2014;Duangthip et al, 2016] since they fulfilled the required features for randomization and allocation. Four studies were at high risk of bias [Vasconcelos, 2011;dos Santos et al, 2012a;Monse et al, 2012;Chu et al, 2014], and 2 studies were at "unclear" risk of bias [Llodra et al, 2005;Seberol and Ökte, 2013]. Color version available online…”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 99%
“…The outcomes were: (1) number of inactive carious surface [Chu et al, 2002a;Llodra et al, 2005;Yee et al, 2009b;Vasconcelos, 2011;Zhi et al, 2012;dos Santos et al, 2014;Duangthip et al, 2016]; (2) number of active carious surface [Llodra et al, 2005;Yee et al, 2009b;Vasconcelos, 2011;Liu et al, 2012;Monse et al, 2012;Seberol and Ökte, 2013;Chu et al, 2014;dos Santos et al, 2014]; (3) dmft index [Chu et al, 2002a;Llodra et al, 2005;Vasconcelos, 2011;dos Santos et al, 2012a;Seberol and Ökte, 2013]; (4) number of teeth with inactive carious lesions [dos Santos et al, 2012a]; (5) number of teeth with new carious lesions [Liu et al, 2012]; (6) number of inactive carious lesions in the first permanent molars [Llodra et al, 2005].…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…Full-mouth rehabilitation of teeth subjected to extreme caries insult has been reported, with SDF providing the opportunity to save many otherwise hopeless teeth [34]. Follow up on SDF treated lesions that have been restored should be approached in the same way as any restoration is monitored; the absence of clinical and radiographic evidence of caries activity or progression will relate to success.…”
Section: Considerations For Use In Operative Dentistrymentioning
confidence: 99%